Dialectical logic of tragedy: revolutionand world war - Duque, Félix (Estudios de Filosofía, 1998)
According to the author, the role of the so-called "Logic o f History" is to easy a deeper understanding of the human historfcal events, and not merelly to justify the situations. He studies the contradictíons and fallacíes the ideals ofthe French Revolution: Freedom, Equality and Brotherhood. He also describes how the most important parties of the twentieth century arase. And finally he intends to clarify the meaning of the world wars, always taking them as confrontations of the mentioned ideals.